Wakaf dan Dasar Hukum Wakaf - Yenni Samri Juliati; Maftah Rizki Addin HRP (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Waqf is one of the people's economic instruments that can be used to empower the people's economy. If used effectively, waqf and other Islamic financial mechanisms such as zakat can be used to improve people's lives. In this way, waqf can be a source of support for the social, economic and religious needs of society. This research was conducted using a descriptive method with a qualitative approach based on data sources from literature studies and observations. The aim of this research is to provide information related to waqf and its legal basis. The research results show that Waqf needs to be developed in a more productive direction, so that it does not undermine aspects of operational financing and administration of waqf assets. On the contrary, it provides multiple benefits to society. The legal basis for waqf is in the Al-Qur'an surah Al-Hajj: 7, Ali Imran: 92, and Al-Baqarah: 291. Meanwhile, the Sunnah of the Prophet is in the famous hadith when Umar donated a piece of land in Khaibar. The various types of waqf are divided into 3 parts, namely waqf based on purpose, based on time limits, and based on use. There are pillars of waqf, namely waqif, Mauquf bih, Mauquf 'alaih, and Sighat. BWI (Indonesian Waqf Board) was formed in order to advance waqf in Indonesia.